KERAGAMAN Fusarium oxysporum f.sp. vanillae YANG BERASAL DARI SULAWESI UTARA BERDASARKAN MEDIA POTATO DEXTORSE AGAR - Arthur ., Pinaria; Max ., Ratulangi; Guntur ., Manengkey (EUGENIA, 2020)
Indonesia is the second largest vanilla producer in the world. Vanillin produced from the drying process of vanilla fruit is the second most valuable commodity in the food and beverage industry in the world. The main obstacle for vanilla cultivation in Indonesia is the attack of vanilla stem rot (BBV). The cause of disease (pathogen) BBV in Indonesia is Fusarium oxysporum f.sp. vanillae. Therefore, it is very important to obtain information about the population of the pathogen Fusarium oxysporum f.sp. vanillae to support the successful assembly of vanilla varieties that are resistant to Fusarium oxysporum f.sp. vanillae. Currently, information on the diversity of the pathogenic population of Fusarium oxysporum f.sp. vanillae in North Sulawesi Province is unknown. This study reports the diversity of the pathogenic population of Fusarium oxysporum f.sp. vanillae originating from North Sulawesi. Samples of stem rot were taken from several villages in Minahasa and Southeast Minahasa and South Minahasa districts. The stem rot samples were taken to the laboratory for isolation and identification. The variation observed was based on the appearance of the isolates on PDA (potato dextrose agar) media. The results showed that the appearance of the isolate Fusarium oxysporum f.sp. vanillae varies based on PDA media.